Assessment of different pools of organic carbon for better C management in cotton-growing shrink-swell soils of Jalgaon district, Maharashtra - GAJARE, A S; MANDAL, D K; PRASAD, JAGDISH (The Indian Journal of Agricultural Sciences, 2016)
Information on dynamics of soil organic carbon (SOC) in agricultural soils is important for sustained crop productivity, maintenance of soil health and alleviating the climate related stress. Researchers have found that oxidizable soil organic carbon (SOC) fractions are more important in maintaining the soil quality than total organic carbon (TOC). The SOC measured by Walkley and Black method is not sensitive to assess soil quality, but labile fractions of TOC is directly related to the soil productivity and quality. It is therefore, imperative to find out its quantum of SOC and fractions of TOC for better C management and carbon sequestration. In such an endeavour, a case study on carbon dynamics was undertaken for cotton-growing shrink-swell soils of Jalgaon district, Maharashtra, to quantify the SOC and its fractions in TOC and their interrelation with the crop yield. The surface (0-30 cm) soil samples (75) were collected from dominant cotton-growing shrink- swell soils in 2011-12 and analyzed for SOC, very labile carbon (VLC), labile carbon (LC), less labile C (LLC) and non-labile C (NLC). Factorial relationship between SOC with TOC and their relationship with crop yield was worked out. The result indicated that VLC, LC, LLC and NLC contributed to the tune of 15.33%, 11.85%, 51.15% and 21.07% of the TOC, respectively. The dichromate oxidizable SOC (y) was found linearly related to the TOC (x) by the equation, y = 0.782x + 0.025 (RÂ² = 0.932), indicating that oxidizable SOC comprised 78.2 % of the TOC, in other words, a correction factor of 1.278 (inverse of the slope of linear regression line) may be used to convert SOC values in shrink-swell soils of Jalgaon. The crop yield was closely related to the SOC (r = 0.642) compared to TOC (r = 0.610). Considering the maximum and minimum cotton yield, the threshold value and maximum value of SOC were worked out to be 5.688 and 8.312 g C/kg, respectively, reflecting the carbon sequestrations potential of soils. Among the different fractions, VLC was found to be well correlated (r = 0.512) with the crop productivity. The computed threshold and maximum value for VLC were 0.547 and 2.147 g C/kg, respectively. The study thus establishes that only 27.18 % of active carbon (VLC+LC) are important for the crop production in cotton- growing shrink-swell soils.